Measurements of charged current lepton universality and |Vus| using tau lepton decays to e−ν[bar]eντ, μ−ν[bar]μντ, π−ντ, and K−ντ - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review letters, 2010)
Using 467 fb−1 of e+e− annihilation data collected with the BABAR detector, we measure B(τ−→μ−¯νμντ)B(τ−→e−¯νeντ)=(0.9796±0.0016±0.0036), B(τ−→π−ντ)B(τ−→e−¯νeντ)=(0.5945±0.0014±0.0061), and B(τ−→K−ντ)B(τ−→e−¯νeντ)=(0.03882±0.00032±0.00057), where the uncertainties are statistical and systematic, respectively. From these precision τ measurements, we test the standard model assumption of μ−e and τ−μ charge current lepton universality and provide determinations of |Vus| experimentally independent of the decay of a kaon.